2010
DOI: 10.1177/0192623310367805
|View full text |Cite
|
Sign up to set email alerts
|

New Findings Concerning Eosinophilic Substance Deposition in Mouse Nasal Septum

Abstract: An eosinophilic substance (ES) is usually observed in the mouse nasal septum. In contrast to textbooks and one report describing ES as amyloid, a previous study by the authors revealed that ES is not amyloid but consists of collagen and an amorphous material. Furthermore, it was suggested that the amorphous material was produced by clear HE-stained nasal gland epithelial cells present at the dorsal portion directly above the vomeronasal organ. In this histological examination, ES deposition showed sex differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Similar lesions were previously diagnosed as an “eosinophilic substance” 11 , 12 , 13 . The material was reported to be Congo red negative, pale blue with Masson’s trichrome and dark magenta with PAS.…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancesupporting
confidence: 61%
See 1 more Smart Citation
“…Similar lesions were previously diagnosed as an “eosinophilic substance” 11 , 12 , 13 . The material was reported to be Congo red negative, pale blue with Masson’s trichrome and dark magenta with PAS.…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancesupporting
confidence: 61%
“…After the presentation, there was discussion about whether or not to rename this lesion as “nasal septum hyalinosis,” since it has already been reported in the literature three times as “eosinophilic substance” by Doi et al 11 , 12 , 13 A revote resulted in nasal septum hyalinosis (48%), eosinophilic substance (46%), nasal gland proteinosis (3%), interstitial hyalinosis (2%), nasal gland secretion (2%), amyloid (0%) and others (0%). These voting results indicate that all audience members agreed that this lesion was not amyloid, although this is the diagnosis in the current INHAND document 14 .…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancementioning
confidence: 99%
“…4.18). Doi et al (2010) have reported sex differences in the occurrence of eosinophilic substance in the nasal turbinates of B6C3F1 mice, with males showing a greater degree of deposition than females. Inflammatory changes in the turbinates occasionally occur in association with foreign bodies, infection or injury (Herbert & Leininger 1999) and may be associated with dysplastic dental changes encroaching into the nasal passages .…”
Section: Respiratory Systemmentioning
confidence: 99%
“…This lesion has been previously diagnosed as “eosinophilic substance” (ES) (Doi et al 2007, 2009, 2010). Present within the mouse nasal septum, it increases in volume with age (which plateaus over time), is more intense in males, and is not associated with degeneration or inflammation.…”
Section: What Is That Eosinophilic Material?mentioning
confidence: 99%